PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA DENGAN CREATIVE WORK BEHAVIOR SEBAGAI VARIABEL INTERVENING (Studi Pada Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Diponegoro Semarang) - Ayu Tamarasanti, Mentari; Ratnawati, Intan (Faculty of Economics and Business Diponegoro University, 2021)
This study aims to analyze the effect of entrepreneurship education on entrepreneurial intention with creative work behavior as mediators. This study uses entrepreneurship education as independent variable, entrepreneurial intention as the dependent variable, and creative work behavior as intervening variable. This study took a study on students of the Faculty of Economics dan Business, Diponegoro University, Semarang. The sample in this study amounted to 120 respondents who were all students of the 2016 Faculty of Economics dan Business Faculty of Diponegoro University dan had taken the entrepreneurship courses. Partial Least Square (PLS) method as statistical tools used in this research. The results of the study are as follows: 1) There are significant and positive effects of entrepreneurship education on entrepreneurial intention, this is indicated by T statistic 4,774 (p < 0,05). 2) There are significant and positive effects of the entrepreneurship education on the creative work behavior, this is indicated by T statistic 7,918, (p < 0,05). 3) There are significant dan positive effects of the creative work behavior on the entrepreneurial intention, this is indicated by T statistic 9,281 (p < 0,05). The results of the mediation testing also show a VAR value of 0.617114 (VAR <0.8), which means that the role of the creative work behavior variable as a mediating variable is partial mediation, in which the entrepreneurial education variable is able to directly influence the entrepreneurial intention variable without going through or involving the mediator variable creative work behaviors.